PROGRAM PENDAMPINGAN PEMBERDAYAAN KELOMPOK DASAWISMA DALAM MENINGKATKAN PENDAPATAN RUMAH TANGGA MELALUI PENGOLAHAN LIMBAH ORGANIK RUMAH TANGGA: PENGOLAHAN SAMPAH ORGANIK MENJADI ECO-ENZYM - Diah Pranitasari; Doddi Prastuti; Pristina Hermastuti S; Kus Tri Andyarini; Enung Siti Saodah; Iman Sofian Suriawinata (Jurnal Abdimas Bina Bangsa, 2023)
The Community Service Program is conducted continuously for 5 years. It is a continuation of a previously implemented Community Service Program and represents the second year of the program. In the first year, training was provided on the processing of household organic waste into planting media. This second-year Community Service Program aims to empower Dasawisma groups in increasing household income through the conversion of household organic waste into eco-enzymes. Eco-enzymes are often referred to as a versatile liquid because they can be used in households, agriculture, livestock, and industry. Each activity is accompanied by a mentoring program to ensure the successful implementation and provide guidance throughout. The short-term outcome of this community service activity is that Dasawisma groups in the Ciracas sub-district of East Jakarta are capable of processing organic waste into eco-enzymes. In the long term, it is hoped that Dasawisma groups in the Ciracas sub-district of East Jakarta will be able to utilize the results of organic waste processing to enhance their supplementary income